Droga Polski do euro: w poszukiwaniu spójności monetarnej - Słobodzian, Ludmiła; Stępińska, Monika (Poland's Road to Euro: in Search of Monetary Cohesion, 2008)
This article, in one way, evaluates the course and general socio-economic results of market-oriented transformation in Poland after 1989, in second, our preparation for accession to the European Monetary Union. The system transformation was in our country a huge experiment with changes of radical character. The transformation of an economy implies overall and breakthrough change to the general conditions of doing business by all companies and entities. The post-communist transformation aims at developing a free market economy. Consequently, the following elements have to undergo changes: the mechanism of allocating resources, the dominant forms of ownership as well as money in an economy. The following elements are usually referred to as economic transformation factors: macroeconomic stabilization, microeconomic liberalization, and a radical institutional restructuring combined with privatization. The discussion on Poland's economic transformation focuses on two controversial issues: one concerns current economic policies - monetary and fiscal, while the other refers to changes of economy's micro- and macroeconomic foundations. Therefore, Poland's economy should enter a next phase of its transformation, based on new macroeconomic policies, and new ways of developing the economy's micro- and macroeconomic foundations. Poland's accession to the European Monetary Union requires meeting of all five criteria of macroeconomic convergence determined in the Maastricht Treaty on establishment of the European Union: three monetary criteria-stability of general level prices - inflation, interest rate and stability of foreign exchange rate, as well as two fiscal criteria - budget deficit and public debt. Eurozone membership may turn to be attractive for Poland in further future (but not necessarily before 2012) after overcoming institutional stiffness of the Stability and Growth Pact and the policy of the European Central Bank, after acceptance of new consensus regarding the priority of economic growth in euro zone and the entire European Union, including achieving full employment and maintaining dynamic financial stabilization in a longer time horizon. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 101-113